Traditional resources and tools for modern drug discovery – Book Review - Yudha SY, Muhammad Bima; Mumtaziyah, Aisyah; Gita, Bhagavad (Ethnobotany Research and Applications, 2025)
A review of Traditional resources and tools for modern drug discovery: ethnomedicine and pharmacology. Springer Nature Singapore Pte Ltd. pp 662. EUR €199.99 (Hardcover). ISBN 978-981-97-4599-9 (hardcover), ISBN 978-981-97-4602-6 (softcover), ISBN 978-981-97-4600-2 (eBook). The book Traditional resources and tools for modern drug discovery: ethnomedicine and pharmacology is a well-structured and insightful exploration of how traditional medicinal resources continue to shape modern drug discovery. It gradually builds from foundational ethnobotanical concepts to advanced pharmaceutical applications, offering a cohesive narrative that demonstrates the importance of integrating indigenous knowledge with contemporary scientific research.